PENGARUH WORK OVERLOAD, DAN WORK FAMILY CONFLICT TERHADAP JOB EMBEDDEDNESS YANG DIMEDIASI OLEH EMOTIONAL EXHAUSTION PADA TENAGA KESEHATAN RUMAH SAKIT IBU DAN ANAK KOTA BANDA ACEH - Muhammad Asyraf Karami; Nashrillah Nashrillah (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This research aims to measure the effect of work overload and work family conflict on job embeddedness mediated by emotional exhaustion on health workers of Mother and Child Hospital, Banda Aceh. Data were collected through a survey of 130 respondents as sample to represents the research population and used a questionnaire as the data collection instrument. The sampling technique used in this research was probability sampling by type stratified random sampling. Structural Equation Modeling (SEM) was used as analytical method to determine the effect between the variables involved. The study found that work overload and emotional exhasution significantly affects job embeddedness, the study also found  emotional exhaustion mediate the effect of work overload and work family conflict to job embeddedness. Nevertheless, the study did not find a significant effect between work family conflict on job embeddedness.